2018
DOI: 10.1159/000486744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recurrent Acute Kidney Injury on Patient Outcomes

Abstract: Background/Aims: Recurrent acute kidney injury (AKI) is common among patients after a first hospitalized AKI. However, little is known about the prognosis of recurrent AKI episodes in chronic kidney disease (CKD) development, cardiovascular events and mortality. Methods: A retrospective study included patients admitted to our Hospital from 2000 to 2010. AKI was defined according to the Acute Dialysis Quality Initiative criteria. In the follow-up period after the first AKI episode, clinical, laboratory data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
0
31
0
2
Order By: Relevance
“…We further found that one fifth of the patients developed recurrent AKI and more than one third developed AKD. In the general adult population, recurrent AKIs have been associated with increased risk of cardiovascular events, mortality, and development of CKD in the long term (31). The clinical relevance of AKD is more obscure.…”
Section: Discussionmentioning
confidence: 99%
“…We further found that one fifth of the patients developed recurrent AKI and more than one third developed AKD. In the general adult population, recurrent AKIs have been associated with increased risk of cardiovascular events, mortality, and development of CKD in the long term (31). The clinical relevance of AKD is more obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size of studies ranged from 170 to 453,475 (median 2,353; IQR 370.5-15,646.8) patients. Ascertain- ment of AKI and r-AKI was obtained through medical records [15][16], health-care databases [4,5,9,17], regional administration database [6,18], or national data registries [19]. Studies used varying definitions of AKI, based on serum creatinine: RIFLE [6,9,16], KDIGO [5,15], or AKIN criteria [4,[18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Newcastle-Ottawa scale, 6 of the 10 studies were rated overall good quality (6-8 stars) [4-6, 15, 18-19], 3 studies were deemed fair quality (5-6 stars) [16,17,20], and 1 study was rated poor quality (0-5 stars, with 0 stars in the comparability domain) [9]. Online supplementary Table S2 presents quality assessment domains for each study.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…AKI was defined according to the KDIGO definition. 7 As per 2011 Renal Association guidelines, 9 and recent articles, [22][23][24][25] baseline creatinine was defined as the lowest creatinine level recorded within 3 months. If a 3-month creatinine was not available, then AKI was not diagnosed, assuming other criteria were not met.…”
Section: Resultsmentioning
confidence: 99%